Managing human resources - Gomez-Mejia, Luis R. (Pearson/Prentice Hall, 2007)
Summary: Using a managerial perspective, the book illustrates the role and impact of technology on globalization, compensation, legal, safety, and health issues."--BOOK JACKET.